Temporal Muscle Thickness as a Prognostic Marker in a Real‐Life Cohort of Newly Diagnosed MGMT Promoter Methylated Glioblastoma: A Multicentric Imaging Analysis - Lazaros Lazaridis; Christoph Moenninghoff; Elisabeth Bumes; Dorothee Cäcilia Spille; Michael Müther; Tim Schulz; Sina Heider; Sarina Agkatsev; Teresa Schmidt; Tobias Blau; Christoph Oster; Walter Stummer; et al. (Cancer Medicine, 2025)
ABSTRACT Introduction Prior research has identified temporal muscle thickness (TMT) as a prognostic marker in glioblastoma. Nonetheless, implementation in daily clinical practice is complicated due to the heterogeneity of previous studies. We performed a multicentric analysis aiming to validate recently proposed sex‐specific cutoff values using a homogeneous cohort of newly diagnosed MGMT promoter methylated glioblastoma patients; we included a balanced control cohort for comparison. Materials and Methods TMT was measured at baseline using the initial preoperative/postoperative magnetic resonance images (MRIs) and in disease course using the first MRI after radiotherapy. Patients were divided by sex and TMT into “at risk of sarcopenia” or “normal muscle status.” Kaplan–Meier and multivariable Cox regression analysis was used for survival correlation. Results In total, n = 126 patients were included (n = 66 treated with CCNU/temozolomide, n = 60 with single‐drug temozolomide). Patients with normal muscle mass at baseline had significantly prolonged survival (median overall survival: 44.2 months versus 16.7 months with CCNU/temozolomide, and 29.5 months versus 17.4 months with single‐drug temozolomide) compared to those at risk of sarcopenia. In a multivariable Cox regression analysis, normal muscle mass and an initial age at diagnosis of < 50 years emerged as significant prognostic markers. Longitudinally, survival was longest in patients with lack of TMT decline over the disease course. Discussion This analysis confirms TMT as an important prognostic marker in glioblastoma in two real‐life cohorts. However, in order to establish TMT assessment as a routine marker for patient selection and therapeutic measures, further validation in prospective controlled trials is necessary.